10 kHz ps 1342 nm laser generation by an electro-optically cavity-dumped mode-locked Nd:YVO4 laser. (January 2017) - Chen, Ying; Liu, Ke; He, Li-jiao; Yang, Jing; Zong, Nan; Yang, Feng; Gao, Hong-wei; Liu, Zhao; Yuan, Lei; Lan, Ying-jie; Bo, Yong; Peng, Qin-jun; et al.
Abstract: We have demonstrated an electro-optically cavity-dumped mode-locked (CDML) picosecond Nd:YVO4 laser at 1342 nm with 880 nm diode-laser direct pumping. At a repetition rate of 10 kHz, an average output power of 0.119 W was achieved, corresponding to a pulse energy of 11.9 μJ. Compared with the continuous wave mode-locking pulse energy of 17.5 nJ, the CDML pulse energy was 680 times higher. The pulse width was measured to be 33.4 ps, resulting in the peak power of 356 kW. Meanwhile, the beam quality was nearly diffraction limited with an average beam quality factor M 2 of 1.29. Highlights: A cavity-dumped mode-locked Nd:YVO₄ laser at 1342 nm was firstly reported. At 10 kHz, pulse energy of 11.9 μJ with beam quality M 2 of 1.29 was achieved. The pulse energy was 680 times higher than that of the CW mode-locking. The pulse width was 33.4 ps, resulting in the peak power of 356 kW. This compact ps laser is suited for physics, bioscience and material processing.